Dural sac area is a more sensitive parameter for evaluating lumbar spinal stenosis than spinal canal area: A retrospective study. Issue 49 (December 2017) - Lim, Young Su; Mun, Jong-Uk; Seo, Mi Sook; Sang, Bo-Hyun; Bang, Yun-Sic; Kang, Keum Nae; Koh, Jin Woo; Kim, Young Uk
Abstract : Abstract: Narrowing of the dural sac cross-sectional area (DSCSA) and spinal canal cross-sectional area (SCCSA) have been considered major causes of lumbar central canal spinal stenosis (LCCSS). DSCSA and SCCSA were previously correlated with subjective walking distance before claudication occurs, aging, and disc degeneration. DSCSA and SCCSA have been ideal morphological parameters for evaluating LCCSS. However, the comparative value of these parameters is unknown and no studies have evaluated the clinical optimal cut-off values of DSCSA and SCCSA. This study assessed which parameter is more sensitive. Both DSCSA and SCCSA samples were collected from 135 patients with LCCSS, and from 130 control subjects who underwent lumbar magnetic resonance imaging (MRI) as part of a medical examination. Axial T2-weighted MRI scans were acquired at the level of facet joint from each subject. DSCSA and SCCSA were measured at the L4-L5 intervertebral level on MRI using a picture archiving and communications system. The average DSCSA value was 151.67 ± 53.59 mm 2 in the control group and 80.04 ± 35.36 mm 2 in the LCCSS group. The corresponding average SCCSA values were 199.95 ± 60.96 and 119.17 ± 49.41 mm 2 . LCCSS patients had significantly lower DSCSA and SCCSA (both P < .001). Regarding the validity of both DSCSA and SCCSA as predictors of LCCSS, Receiver operating characteristic curve analysis revealed an optimal cut-off value for DSCSA of 111.09 mm 2, with 80.0% sensitivity, 80.8% specificity, and an area under the curve (AUC) of 0.87 (95% confidence interval, 0.83–0.92). The best cut off-point of SCCSA was 147.12 mm 2, with 74.8% sensitivity, 78.5% specificity, and AUC of 0.85 (95% confidence interval, 0.81–0.89). DSCSA and SCCSA were both significantly associated with LCCSS, with DSCSA being a more sensitive measurement parameter. Thus, to evaluate LCCSS patients, pain specialists should more carefully investigate the DSCSA than SCCSA.